1997
DOI: 10.1001/jama.1997.03550100049038
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Adolescents From Harm

Abstract: Family and school contexts as well as individual characteristics are associated with health and risky behaviors in adolescents. The results should assist health and social service providers, educators, and others in taking the first steps to diminish risk factors and enhance protective factors for our young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
595
3
11

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 2,635 publications
(656 citation statements)
references
References 0 publications
28
595
3
11
Order By: Relevance
“…Elements that determine the quality of such relationships (e.g., having a sense of connectedness, good communication, support, involvement, and belonging within the group) can help protect against risky health behaviours and mental health problems. The family is one of the most important groups from this perspective, with adolescents who report high levels of family connectedness reporting lower levels of cigarette, alcohol, and marijuana use (Resnick et al, 1997). Smoking (Wang, Fitzhugh, Westerfield, & Eddy, 1995) and alcohol use (Bonnie & O'Connell, 2004) can be discouraged through healthy family norms and attitudes, as well as through healthy behaviour modeling.…”
Section: Addressing Socially Motivated Adolescent Addictive Behavioursmentioning
confidence: 99%
See 2 more Smart Citations
“…Elements that determine the quality of such relationships (e.g., having a sense of connectedness, good communication, support, involvement, and belonging within the group) can help protect against risky health behaviours and mental health problems. The family is one of the most important groups from this perspective, with adolescents who report high levels of family connectedness reporting lower levels of cigarette, alcohol, and marijuana use (Resnick et al, 1997). Smoking (Wang, Fitzhugh, Westerfield, & Eddy, 1995) and alcohol use (Bonnie & O'Connell, 2004) can be discouraged through healthy family norms and attitudes, as well as through healthy behaviour modeling.…”
Section: Addressing Socially Motivated Adolescent Addictive Behavioursmentioning
confidence: 99%
“…They were also more likely to delay sexual initiation, and tended to Running head: GROUP IDENTIFICATION AND ADDICTIVE HEALTH BEHAVIOURS IN ADOLESCENTS 8 report lower levels of cigarette, alcohol, and marijuana use (Resnick et al, 1997).…”
Section: Addressing Socially Motivated Adolescent Addictive Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Shann (1999) found that a positive school climate results in positive relationships among teachers and students and positive student attitude towards school. In addition, research has shown that if students feel accepted and included in their schools, they develop positive attitudes and emotions towards school and learning (Osterman, 2000;Resnick et al, 1997). Boxes 4 and 5 show index scales that are used to represent these attitudes.…”
Section: Student Attitudes Towards School and Learningmentioning
confidence: 99%
“…potentially overlapped as risk behaviors among students (Resnick, 1997) An additional research finding related to the social, physical, and economic benefits of "abstinence until marriage, " moved the expectation for sexual restraint away from a moral viewpoint.…”
mentioning
confidence: 99%